A comprehensive review on emerging trends in the dynamic evolution of digital addiction and depression - Karakose, Turgut; Yıldırım, Bilal; Tülübaş, Tijen; Kardas, Abdurrahman (Frontiers in Psychology, 2023)
Using digital addiction as an umbrella term to cover any type of addictions to digital technologies such as the internet, smartphones, social media, or video games, the current study aimed to reveal the intellectual structure and evolution of research addressing digital addiction-depression relationship. The study combined bibliometric and science mapping analysis methods for this purpose. Data for the study was gathered from Web of Science Core Collection after a comprehensive process of data search/extraction, and 241 articles were included in the final data set. A period-based, comparative science mapping analysis was performed using the SciMAT software. The analysis of data over three periods, Period 1 (1983-2016), Period 2 (2017-2019), and Period 3 (2020-2022) showed that internet addiction was the most significant theme across all three periods, which was followed by social media addiction. Depression, which emerged as a significant theme during Period 1, was later covered under anxiety disorder theme. Research interest was mostly on factors related to both addiction and depression such as cognitive distortion, insomnia, loneliness, self-esteem, social support, alexithymia, as well as cybervictimization or academic performance. The results suggested that much research is warranted on the digital addiction-depression relationship in different age cohorts, especially children and elderly. Similarly, the current analysis showed that this line of research particularly focused on internet, gaming and social media addiction, and evidence with regard to other types of digital addiction or related compulsive behaviors was almost absent. In addition, research was mostly inclined to understanding cause-effect relationships, which is significant, but preventive strategies seemed to be barely addressed. Likewise, the smartphone addiction-depression relationship arguably garnered less research interest, so future research would contribute to the field in this respect.